Embodying the unconscious: A new paradigm for the study of consciousness - Colelli, Jacopo; Di Bernardo, Mirko (Rivista Italiana di Filosofia del Linguaggio, 2023)
Within cognitivist reflection a heated debate is centered today between those who consider legitimate to adopt a fundamentalism that returns to the neurobiological dimension and those who instead assume the non-reducibility of the phenomenological explanation to the physiological one. In the present contribution, an alternative perspective is outlined, which we have termed “hermeneutics of the living”. The research motivates the overcoming of fundamentalist assumptions in favor of an epistemological and ontological pluralism that enhances the continuity between the phenomenon of life, which can be investigated from its physiological components, and that of consciousness, which can instead be described with the methods and languages of phenomenology, anthropology, psychology, and the existential dimension. The moment of methodological reductionism, then, prepares for a holistic return in which the various perspectives are integrated into a description that is optimal and complete. The object of such an inquiry is the living-being understood as a whole, a radically embodied subjectivity that entertains an intentional relationship with its world-environment. The contribution presents the phenomenon of consciousness as the integral that encompasses the multiple activities of a living body in continuous resonance with the various affordances of the world-environment. The nature of this relationship can be investigated from a careful consideration of the genetic modes through which conscious experience is temporally constituted. Finally, we have attempted to demonstrate why the phenomenological method is the most appropriate epistemological tool to enrich neurobiological research within a renewed scientific enterprise that is, by its very nature, interdisciplinary.